2010
DOI: 10.5539/ijbm.v5n4p53
|View full text |Cite
|
Sign up to set email alerts
|

Citizenship in the Workplace : Examining Work Attitudes as Predictors Among French Employee

Abstract: Organizational citizenship behaviour (OCB) has been a subject of continually increasing interest in academic managerial literature. While most current research comes from the United States, several scholars have argued for the need for global data. As Podsakoff, MacKensie, Paine and Bachrach (2000, p. 556) insist, "cultural context may affect a) the forms of citizenship behaviour observed in organizations and b) the strengths of relationships between citizenship behaviour and its antecedents and consequences."… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 67 publications
3
10
0
Order By: Relevance
“…Thus, occupational stress is found not to be a significant trigger of organizational citizenship Behaviour of Bankers. This finding agrees with Paillé (2010) who reported that there was no significant relationship between Organizational citizenship Behaviour and Occupational stress.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, occupational stress is found not to be a significant trigger of organizational citizenship Behaviour of Bankers. This finding agrees with Paillé (2010) who reported that there was no significant relationship between Organizational citizenship Behaviour and Occupational stress.…”
Section: Discussionsupporting
confidence: 92%
“…Cropanzano, Howes, Grandey, & Tooth (1997) found a significant negative relationship between stressful work and organizational citizenship behaviour. Paillé (2010) found no statistically significant relationship between Organizational citizenship Behaviour and Occupational stress.…”
Section: Introductionmentioning
confidence: 66%
“…To further refine the understanding of OCB in Mexico, future research should include confirmatory factor analysis using new data sets to analyze criterion validity (for example, convergent and discriminant validity) in line with previous research efforts (Coyne & Ong, ; Farh, Earley, & Lin, ; Farh, Zhong, & Organ, ; Lievens & Anseel, ; Ortiz, ; Paillé, , ). This would enable researchers to offer a better empirical understanding of organizational behavior and address its characteristics in a broader global context and uncover indigenous dimensions of OCB in other cultures.…”
Section: Findings Offer Managerial Guidancementioning
confidence: 97%
“…A stream of OCB research has focused on cultures outside the United States and other Western nations (for example, Farh, Earley, & Lin, ; Farh, Zhong, & Organ, ; Kim, ; Lievens & Anseel, ; Paillé, , ). Meanwhile, a number of cross‐cultural studies have explored possible similarities and differences in OCB across borders.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that attitudes influence the performance of OCB. Therefore, it is recommended to continue to investigate the phenomenon so as to reveal additional factors that have an influence on OCB [8,9].…”
Section: Introductionmentioning
confidence: 99%